Recriar: design, infância e brincadeiras não binárias - Ferreira, Georgia Costa (My University, 2021)
The ingrained culture that we see in society reinforces gender binarism, something that persists even in contemporary times. From the perspective of childhood, we see that children from 4 years of age onwards are pressured to perform actions and choices according to their anatomy according to social judgment. Therefore, this work has the objective of a project that includes brand, product and service, which uses the tools of multisensory design and their interconnections to contribute to freedom of expression in non-binary games for children. This using as a methodology the feminist approach Dandelion, together with Design Thinking. With a result that covers the areas of brand, product and service, which aims to give freedom to children at the time of play, giving them autonomy to create their way of playing through the product, and a service that would take more information to tutors, to understanding of the brand concept, and new challenges for children. [resumo fornecido pelo autor]
O capitalismo e o patriarcado reforçam o binarismo de gênero, algo que perdura mesmo na contemporaneidade. Na infância vemos que crianças são pressionadas - desde cedo - a realizarem ações e escolhas de acordo com padrões e scripts de gênero, conceito elaborado por Felipe (2019). O objetivo deste trabalho é refletir sobre as interconexões entre design e infância, por meio de um projeto que contemple marca, produto e serviço, utilizando ferramentas do design multissensorial para contribuir com a liberdade de expressão nas brincadeiras não-binárias. A metodologia foi desenvolvida a partir da Dandelion, uma abordagem feminista e interseccional para o design, junto com o Design Thinking. Como resultado, foi desenvolvido o projeto Recriar, que propõe atividades lúdicas não-binárias para incentivar a autonomia e liberdade de expressão para crianças em suas brincadeiras. [resumo fornecido pelo autor]
Keywords: Design; Infância; Brincadeiras; Identidade de gênero - Crianças